دور الاعلام في تنشيط حركة التنمية السياحية في العراق (Journal of Planner and Development, 2005)
the research aims at exposing the role of information to activate tourism development and its movement in iraq < throught employing the importance of information elements , tools and rotations with tourism development with their impacts on it .